Telecommunications Infrastructure in the Arctic; A Circumpolar Assessment (Arctic Council Secretariat, 2017)
This report presents the Task Forces investigation and analysis into the technologies presently available to users, and identifies gaps in the infrastructure. The report also provides an overview of each State's telecommunications priorities. Changes occur rapidly in the telecommunications industry, and it is inevitable that some of the information or details contained in this report will quickly become outdated. Readers should view this report as a "snapshot" of the state of telecommunications infrastructure in the Arctic, and should certainly be attentive to ongoing developments.